2011
DOI: 10.5665/sleep.1270
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Sleepiness During Real Driving at Night—A Study of Driving Performance, Physiology and Subjective Experience

Abstract: Night driving is associated with high levels of subjective, electrophysiologic, and behavioral sleepiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 41 publications
12
49
0
Order By: Relevance
“…Yet simulators like the YDS are known to overestimate the performance deficit seen in real driving (Contardi et al, 2004). Confirming this, in a recent study of real driving, increases in subjective sleepiness (on the KSS) did not result in the expected increase in lane variability suggested from simulator studies (Sandberg et al, 2011). Therefore, although the current findings infer changes in driving ability, on-road testing is required to determine exactly how these results relate to real driving performance.…”
Section: Discussionsupporting
confidence: 82%
“…Yet simulators like the YDS are known to overestimate the performance deficit seen in real driving (Contardi et al, 2004). Confirming this, in a recent study of real driving, increases in subjective sleepiness (on the KSS) did not result in the expected increase in lane variability suggested from simulator studies (Sandberg et al, 2011). Therefore, although the current findings infer changes in driving ability, on-road testing is required to determine exactly how these results relate to real driving performance.…”
Section: Discussionsupporting
confidence: 82%
“…Intriguingly, overall performance in sleep-deprived subjects is highly unstable, oscillating back and forth from normal levels to catastrophic mistakes (Doran et al, 2001; Zhou et al, 2011), just as would be expected given the stochastic, all-or-none occurrence of local sleep. In addition, the occurrence of local sleep at times in subcortical, arousal-promoting systems, and at other times in specific cortical areas, could explain the occasional dissociation between overall vigilance and specific cognitive functions under conditions of sleep deprivation (Blatter et al, 2005; Sagaspe et al, 2007; Sandberg et al, 2011). …”
Section: Some Open Issuesmentioning
confidence: 99%
“…Some studies have examined less precise but more ecologically valid measures. For example, night-time driving, which coincided with an increase in sleepiness, was found to be associated with an increase in lateral variability and reduced speed while driving (Sandberg et al 2011). In a review of California Department of Motor Vehicles driving records and reports, one study found that short sleepers are not at a higher risk for accidents or other violations (Kripke and Rex 2002).…”
Section: Introductionmentioning
confidence: 99%